PEMBERDAYAAN EKONOMI MELALUI PELATIHAN EKSPOR PADA KELOMPOK UMKM DAN SMK DI KELURAHAN DUREN JAYA KECAMATAN BEKASI TIMUR KOTA BEKASI PROVINSI JAWA BARAT - Verawati, Kencana; Rahmayanti, Henita (JURNAL WIDYA LAKSANA, 2021)
Many small and medium entrepreneurs hope to develop their business by exporting their products to a wider market. However, rarely do entrepreneurs think of being able to try out the export market in order to expand their market reach. Even this tax issue between exports and imports has different regulations. When we import goods, almost all goods was subject to import taxes. Meanwhile, when exporting our products overseas, not all products are subject to export taxes and customs duties. The methods used was (1) preparation (2) implementation and (3) reporting. With this training, we hope that the public will understand more that the constraints during export and import were not too difficult to apply. We chose Bekasi city as a place for this export training, not only because of the mapping and work locations that have been determined by the university, but also because this area had many small and medium business community pockets.